Individuals : Post-movement art in America - Sondheim, Alan; Abish, Walter; Acconci, Vito; Anderson, Laurie; Askevold, David; Aycock, Alice; Horvitz, Robert; Lucier, Alvin; Mayer, Rosemary; Metz, Mike; Morton, Ree; Oppenheim, Dennis; et al. (New York : E.P. Dutton & Co, Inc. New York, 1977)
Abish, Walter ; Acconci, Vito ; Anderson, Laurie ; Askevold, David ; Aycock, Alice ; Horvitz, Robert ; Lucier, Alvin ; Mayer, Bernadette ; Mayer, Rosemary ; Metz, Mike ; Morton, Ree ; Oppenheim, Dennis ; Piper, Adrian ; Simonds, Charles ; Wilson Kitchel, Nancy
Korte biog. p. 313-316
Engels
boek
Keywords: Verenigde Staten; U.S.A.